A REVIEW OF COASTAL PALAEOCLIMATE AND RELATIVE SEA-LEVEL RECONSTRUCTIONS USING δ13C AND C/N RATIOS IN ORGANIC MATERIAL - Lamb A.L.; Leng M.J.; Wilson G.P. (My University, 2006)
Holocene reconstructions of relative sea-level (RSL) and environmental change in the coastal zone have become progressively more numerous since the importance of assessing possible future sea-level rises has become apparent. Traditionally this has been achieved using a combination of biological and physical indicators (e.g. pollen, diatoms, foraminifera, grain size, etc.). In some circumstances, microfossils can be rare or absent from Holocene sediments and in these cases carbon isotope ratios (δ13C) and organic carbon to total nitrogen ratios (C/N) can be used because they have the potential to provide information as to the origin of organic material preserved in coastal environments. The distinction in δ13C and C/N of the various sources of carbon to estuarine sediments has led to its wide use as a tracer of carbon pathways and storage in estuaries. More recently these techniques have been applied to Holocene sediments to decipher changes in palaeocoastal environments and thus position relative to sea-level and/or palaeoriver discharge, which have direct relevance to palaeoclimate. This paper reviews the studies that have utilised this technique and explores examples from a wide range of coastal environments (saltmarshes, estuaries, lagoons, isolation basins and fjords). It also discusses the potential alteration of geochemical signatures as a result of decompositional processes. Organic matter decomposition has been shown to change sediment δ13C and C/N values and thus an understanding of the processes involved is necessary in order to have confidence in the palaeoenvironmental interpretation of Holocene δ13C and C/N. Decompositional shifts in C/N, and particularly δ13C, can occur over a relatively short time-period, however it is the direction of change in δ13C and C/N, rather than absolute values, that is key for interpreting changes in relative sea-level and thus such changes are commonly preserved. © 2005 NERC. Published by Elsevier B.V. All rights reserved.
Keywords: CARBON; COASTAL; DECOMPOSITION; HOLOCENE; ISOTOPE RATIOS; NITROGEN; ORGANIC MATERIAL; Кайнозой::Четвертичная::Голоцен; Cenozoic::Quaternary::Holocene